Peptide stapling by late-stage Suzuki–Miyaura cross-coupling - Gruß, Hendrik; Feiner, Rebecca C.; Mseya, Ridhiwan; Schröder, David C.; Jewgiński, Michał; Müller, Kristian M.; Latajka, Rafał; Marion, Antoine; Sewald, Norbert (Beilstein Journal of Organic Chemistry, 2022)
The development of peptide stapling techniques to stabilise α-helical secondary structure motifs of peptides led to the design of modulators of protein–protein interactions, which had been considered undruggable for a long time. We disclose a novel approach towards peptide stapling utilising macrocyclisation by late-stage Suzuki–Miyaura cross-coupling of bromotryptophan-containing peptides of the catenin-binding domain of axin. Optimisation of the linker length in order to find a compromise between both sufficient linker rigidity and flexibility resulted in a peptide with an increased α-helicity and enhanced binding affinity to its native binding partner β-catenin. An increased proteolytic stability against proteinase K has been demonstrated.
Keywords: accelerated molecular dynamics; halotryptophan; intrinsically disordered peptides; late-stage diversification; macrocyclisation; molecular dynamics; stapled peptides; Suzuki–Miyaura cross-coupling